The Role of lncRNA Crosstalk in Leading Cancer Metastasis of Head and Neck Squamous Cell Carcinoma - Wang, Yu; Wang, Sinan; Ren, Yu; Zhou, Xuan (Frontiers in Oncology, 2020)
Head and neck squamous cell carcinoma (HNSCC) is the 6th most common type of human malignancies. For decades, researches into HNSCC invasion and metastasis dedicated to the study of protein-coding genes. Along with the whole genome and transcriptome sequencing development, long non-coding RNA (lncRNA) has attracted greater attention. Compelling evidence has proved the critical role of lncRNAs in the occurrence and development of HNSCC, by means of epigenetic modifications, regulation of gene transcription and post-transcription level. More importantly, crosstalk between lncRNAs and microRNAs was recently proved to regulate HNSCC metastasis through EMT modification. Based on these, the review will summarize the critical roles of lncRNAs in HNSCC metastasis and the crosstalk between lncRNAs and microRNAs, as well as the detailed regulatory mechanism of the interaction. Thus, a deeper understanding of lncRNA network in cancer metastasis was finally delved in order to provide a rationale and innovative concepts towards new therapeutic strategies for the highly metastatic HNSCC.